Association Between Use of Anti-gout Preparations and Dementia: Nested Case–Control Nationwide Population-Based Cohort Study - Chuang, Tsung-Ju; Wang, Yu-Hsun; Wei, James Cheng-Chung; Yeh, Chih-Jung (Frontiers in Medicine, 2021)
Objectives: Gout is the most common form of inflammatory arthritis and was found to be independently associated with incident dementia in the elderly. However, the associations between anti-gout preparations and dementia were not well studied. Methods: Data were collected from Taiwan’s National Health Insurance Research Database (NHIRD). A 2005-2013 retrospective cohort study was conducted, and all investigated subjects were identified by International Statistical Classification of Diseases and Related Health Problems, 9th Revision, Clinical Modification. Conditional logistic regression was used to evaluate the odds ratio of dementia in relation to different gout preparations (benzbromarone, allopurinol, sulfinpyrazone, probenecid) and number of days of anti-gout preparation use, after adjustment for potential confounding variables. Results: A total of 3242 gout patients with and without dementia were selected from the NHIRD and included in the final analysis after 1:1 matching for age, gender, and diagnosis year of gout. In the anti-gout preparations, only use of Benzbromarone decreased the risk of dementia (adjusted OR, 0.81; 95% CI, 0.68–0.97). The result of the subgroup analysis revealed a trend toward a lower risk of dementia with longer use of benzbromarone. Use of benzbromarone for ≥180 days showed a significantly lower risk of dementia (adjusted OR, 0.72; 95% CI, 0.58–0.89). Moreover, the protective effect was more pronounced in males compared with females. Conclusion: This cohort study reveals that gout patients taking benzbromarone are at a decreased risk of developing incident dementia, especially with longer use and in male. Further prospective trials are warranted to confirm our findings.